ENTRENCHING SUPPLY CHAIN RESILIENCE BEYOND BOUNDARIES: A DYNAMIC FRAMEWORK IN POST-COVID LANDSCAPE (Journal of Technology and Operations Management, 2023)
The unprecedented global impact of the COVID-19 pandemic has heightened the critical significance of supply chain resilience (SCR) within the contemporary supply chain landscape. The body of literature dedicated to SCR has significantly expanded since the early 2000s, with numerous scholars delving into the construction of SCR frameworks based on empirical studies and literature reviews. Despite the usefulness of these frameworks, there has been a notable absence of a generic framework that transcends industry and national boundaries, particularly in light of the disruptive events triggered by the COVID-19 crisis. This study employs the narrative literature review method to intricately integrate itself into the existing SCR literature, conducting a comprehensive analysis, identifying theoretical foundations and empirical discoveries, and synthesizing this knowledge into a cohesive and all-encompassing structure to formulate a conceptual framework for SCR. This generic framework is designed to accommodate the unique characteristics of various supply chains. While the empirical validation of this innovative framework remains pending, it presents a valuable opportunity for scholars to engage in scientific investigations on SCR, building upon the collective insights of their predecessors. Moreover, practitioners can leverage this framework to scrutinize and construct resilient supply chains capable of withstanding future disruptions.